Tree Kangaroos (Dendrolagus sp.) of Papua: Characteristics and Conservation - Prasetyo Budi; Utami Sri; Wahyuni Nenden Sri (E3S Web of Conferences, 2024)
Tree kangaroos (Dendrolagus sp.) are an endemic mammal species in the Papua region. Tree kangaroos are vulnerable to threats, both from habitat conditions (forest destruction, illegal logging) and predators and hunting. Meanwhile, according to the IUCN, its conservation status is in crisis category. The purpose of this paper is to inform the public about the characteristics, behavior, and conservation of tree kangaroos (Dendrolagus sp.) in Papua. It is hoped that over time this information can motivate indigenous Papuans to increasingly care and love tree kangaroos, so that they continue to exist and sustain their regeneration in the tropical rainforests of Papua. Writing using the literature review method. The results of the writing explain that tree kangaroos have several characteristics, including: having a body weight of no more than 6-20 kg, even some are very small, weighing 3 kg. Tree kangaroos tend to live in groups with one dominant male. This marsupialia has a white to yellowish face, the same as the neck to the abdomen, long ears, a tail longer than the body, has long limbs and four very strong clawed fingers. Tree kangaroos experience embryonic dipouse or delayed birth, allowing females to mate again after giving birth or the baby is still in the pouch. The indigenous Papuan community conducts traditional conservation for the survival of tree kangaroos.